The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1678-77572009000700009
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders, voice and oral quality of life in women

Abstract: Some studies have shown a relationship between temporomandibular disorders (TMD) and dysphonia, as well as quality of life in oral health. Objective: The purpose of this study was to investigate the correlation between severity of vocal self-perception and TMD severity and the correlation between oral health-related quality of life impairment and TMD severity. Material and methods: Thirty-three women aged 20 to 40 years, with or without complaint of dysphonia, were recruited at the Bauru campus of the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 16 publications
5
25
0
10
Order By: Relevance
“…Surge como instrumento único de avaliação em 13 estudos: na Jordânia (Al Habashneh et al, 2012); no Brasil (Pereira et al, 2009); Japão (Inukai et al,2010); na China (Zheng et al, 2011); no Irão (Motallebnejad et al, 2011); Finlândia (Miettinen et al, 2012;Rusanen et al, 2012;Silvola et al, 2012); Espanha (Gil-Montoya et al, 2013;Montero et al, 2009;Perea et al, 2013); Nova Zelândia (Thomson et al, 2006) e com indivíduos croatas e eslovenos (RenerSitar et al, 2008). É utilizado em simultâneo com outro instrumento numestudo desenvolvido noCanadá por Locker e Gibson (2005).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Surge como instrumento único de avaliação em 13 estudos: na Jordânia (Al Habashneh et al, 2012); no Brasil (Pereira et al, 2009); Japão (Inukai et al,2010); na China (Zheng et al, 2011); no Irão (Motallebnejad et al, 2011); Finlândia (Miettinen et al, 2012;Rusanen et al, 2012;Silvola et al, 2012); Espanha (Gil-Montoya et al, 2013;Montero et al, 2009;Perea et al, 2013); Nova Zelândia (Thomson et al, 2006) e com indivíduos croatas e eslovenos (RenerSitar et al, 2008). É utilizado em simultâneo com outro instrumento numestudo desenvolvido noCanadá por Locker e Gibson (2005).…”
Section: Resultsunclassified
“…Destaca-se a utilização da variável referente à presença ou número de dentes naturais presente em 10 estudos (Gil-Montoya et al, 2013;Hsu et al, 2014;Inukai et al, 2010;Locker & Gibson, 2005;Montero et al, 2008;Motallebnejad et al, 2011;Perea et al, 2013;Pistorius et al, 2013;Wright, 2009;Thomson et al, 2006;); a presença de dentes deteriorados (cariados), perdidos ou obturados e doenças periodontais em 4 estudos (Montero et al, 2008;Montero et al, 2009;Motallebnejad et al, 2011;Thomson et al, 2006); a má oclusão avaliada em 4 estudos (Hsu et al, 2014;Rusanen et al, 2012;Sardenberg et al, 2011;Silvola et al,2012); a utilização de próteses dentárias em 3 estudos (Montero et al, 2008;Perea et al, 2013;Pistorius et al, 2013;Wright et al, 2009); a xerostomia em 2 estudos (Perea et al, 2013;Thomson et al, 2006); a dor facial em 2 estudos Zheng et al, 2011); as disfunções temporomandibulares em 3 estudos (Miettinen et al, 2012;Pereira et al, 2009;Rusanen et al, 2012) e a dor de dentes em apenas 1 estudo (Rener-Sitar et al, 2008).…”
Section: Resultsunclassified
“…There is evidence that TMJ disorder and/ or dysfunction (TMD) affects voice-related quality-of-life, especially vocal self-perception. Also, any chronic TMD, as in our case, induces cranio-skeletal malalignment and asymmetrical stress patterns, which further complicates the voice-loss issue [1,2].…”
mentioning
confidence: 76%
“…There is evidence that TMJ disorder and/ or dysfunction (TMD) affects voice-related quality-of-life, especially vocal self-perception. Also, any chronic TMD, as in our case, induces cranio-skeletal malalignment and asymmetrical stress patterns, which further complicates the voice-loss issue [1,2].To conclude, for voice dysfunction after contentious TMJ surgery, the anesthesiologist must always collate-andconsider specific information on preoperative voice profile (generation, pitch) and peri-surgical factors (masseter spasm, TMJ dislocation) to arrive at a precise diagnosis, take corrective action, and avoid responses that have their own set of problems.Conflict of interest None. References 1.…”
mentioning
confidence: 85%
“…Although voice is the teacher's work instrument, the health-disease process related to voice is still little understood by this professional, having as consequence little perception of its own self-evaluation and its voice disturbs 6,19-21 . There is a correlation between voice self-perception and temporomandibularjoint dysfunction (TJD) in women, considering that as severe the TJD, higher the vocal disturb perception 25 . The symptoms related to voice presented by the vocal complaint group showed that teachers of the present research may be susceptible to develop voice disturbances and autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%